WORKING WITH DATA WAREHOUSES IN THE MEDICAL FIELD: MODERN SOLUTIONS AND PROMISING TECHNOLOGIES - Egamov Sultanjon Malikovich; Bobonazarov Daler Bakhtiyorovich (Modern American Journals, 2025)
This article highlights the importance, applications, and future trends of database usage in the medical field. It examines the role of electronic health records (EHR), telemedicine, artificial intelligence (AI), and big data in improving healthcare services. The paper also discusses modern methods of storing, processing, and securing medical data, including HIPAA and GDPR standards. The use of medical databases enables personalized patient care, faster diagnostics, and enhanced epidemiological monitoring. Future advancements in genetic testing, IoT devices, and AI-based systems are expected to revolutionize medicine.
Keywords: Medical database, Electronic health records (EHR/EMR), Telemedicine, Artificial intelligence (AI) and machine learning, Big Data, Data privacy (HIPAA, GDPR), Clinical decision support systems (CDSS), Genomics and personalized medicine, IoT (Internet of Things) and real-time monitoring, Blockchain technology.